Design optimization of ironless multi-stage axial-flux permanent magnet generators for offshore wind turbines. Issue 5 (4th May 2017) - Zhang, Zhaoqiang; Nilssen, Robert; Muyeen, S. M.; Nysveen, Arne; Al-Durra, Ahmed
ABSTRACT: Direct-driven ironless-stator machines have been reported to have low requirements on the strength of the supporting structures. This feature is attractive for offshore wind turbines, where lightweight generators are preferred. However, to produce sufficient torque, ironless generators are normally designed with large diameters, which can be a challenge to the machine's structural reliability. The ironless multi-stage axial-flux permanent magnet generator (MS-AFPMG) has the advantages of ironless machines but a relatively small diameter. The objective of this article is to present the design optimization and performance investigation of the ironless MS-AFPMG. An existing design strategy, which employs two- and three-dimensional static finite element analyses and genetic algorithm for machine optimization, is improved with the aim of reducing the calculation load and calculation time. This improved design strategy is used to investigate the optimal ironless MS-AFPMG. Some intrinsic features of this kind of machine are revealed.